Laser Beam Welding of AA5052, AA5083, and AA6061 Aluminum Alloys - A. El-Batahgy; M. Kutsuna (Advances in Materials Science and Engineering)
The present investigation was mainly concerned with characteristics of autogeneous laser butt welding of 2 mm thickness nonheat treatableAA5052-H12,AA5083-H12 and 2 mm, 3 mm thickness heat treatableAA6061-T6aluminum alloys. The effect of laser welding parameters, surface cleaning, filler wire addition, and backing strip on quality of laser welded joints was clarified using 5 kW CO2 laser machine. It was found that all the investigated alloys showed tendencies for porosity and solidification cracking, particularly, at high welding speed (≥4 m/min). Porosity was prevented by accurate cleaning of the base metal prior to welding and optimizing the flow rate of argon shielding gas. Solidification cracking was avoided through two different approaches. The first one is based on the addition of filler metal as reported in other research works. The other new approach is concerned with autogeneous welding using a backing strip from the same base metal, and this could be applicable in production. Preventing solidification cracking in both cases was related mainly to a considerable decrease in the stress concentration at the weld metal center as a result of improving the fusion zone profile. The implementation of the new approach could help in producing weldments with a better quality due to the absence of the filler metal, which is known as a source for hydrogen-related porosity. It can also have a positive economic aspect concerning the manufacturing cost since welding is done without the addition of filler metal. Not only quality and economic positive aspects could be achieved, but also high productivity is another feature since high quality autogeneous weldments were produced with high welding speed, 6 m/min. Hardness measurements and tensile test of AA6061 alloy welds indicated a remarkable softening of the fusion zone due to dissolution of the strengthening precipitates, and this was recovered by aging treatment after welding. For alloys AA5052 and AA5083, softening of the fusion zone due to the loss of its work-hardened condition was much less in comparison with AA6061 alloy.